Distribution network electric vehicle hosting capacity enhancement using anoptimal power flow formulation (2019)
This thesis presents a method based on an optimal power flow (OPF) procedure to determine the maximum Hosting Capacity (HC) of Electric Vehicles (EV) that can be supported by a distribution network. With a focus on the injection control of reactive power, it is possible to maximize the penetration of EV. The presented method is based on linearized power flow equations, allowing a significant reduction in the computational processing times. Two comparisons are presented. The first one is between a non-linear and a linear optimal power flow (OPF) method. Second one, it is comparative analysis between legacy iterative (non-optimized) method of HC and the proposed method. It is applied in the IEEE 13 node test feeder circuit showing its effectiveness and acceptable performance. Results demonstrate that the implemented method enhance the HC measured against a legacy HC method, and decrease the computational time measures against non-linear optimization methods.